2020
DOI: 10.3233/jad-200234
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteic Acid in Blood Can Detect Mild Cognitive Impairment: A Preliminary Study

Abstract: Background: In the treatment of Alzheimer’s disease (AD), it is thought to be most effective to intervene at the earliest and mildest stages. For diagnosis at the earliest and mildest stages, it is desirable to use a biomarker that can be detected by a minimally invasive, cost-effective technique. Recent research indicates the potential clinical usefulness of plasma amyloid-β (Aβ) biomarkers in predicting brain Aβ burden at an individual level. However, it is as yet unproven that accumulation of Aβ necessarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…HCA exhibited very high brain toxicity at low concentrations and overactivated the NMDAR. HCA seemed to be upstream from neurodegeneration in the AD pathology because it was known that an overactive NMDAR promoted amyloid polymerization and tau phosphorylation in AD [247].…”
Section: And Alzheimer's Diseasementioning
confidence: 99%
“…HCA exhibited very high brain toxicity at low concentrations and overactivated the NMDAR. HCA seemed to be upstream from neurodegeneration in the AD pathology because it was known that an overactive NMDAR promoted amyloid polymerization and tau phosphorylation in AD [247].…”
Section: And Alzheimer's Diseasementioning
confidence: 99%
“…A preliminary study suggests that plasma HCA may be a useful indicator as an early diagnostic marker for mild cognitive impairment (MCI). HCA is possibly upstream from neurodegeneration in the Alzheimer’s disease pathology because it promotes amyloid polymerization and tau phosphorylation in AD [ 49 ]. Adequate vitamin B 6 , vitamin B 12 , and folate intakes were significantly associated with better cognitive reserve by affecting methylation levels of specific redox-related genes [ 50 ].…”
Section: Homocysteinementioning
confidence: 99%
“…Furthermore, investigations at ionotropic NMDA and metabotropic glutamate receptors revealed that ROS are produced to a higher extent by HCA than by HCys [128]. In a recent human study, Hasegawa and colleagues considered HCA as an early diagnostic marker of mild cognitive impairment and as more relevant than HCys in this context [129]. Earlier, it has been shown that treatment with an anti-HCA antibody attenuated cognitive impairment in the 3xTg-AD mouse model [130].…”
Section: Hhcys Impact On Cognition In Animal Modelsmentioning
confidence: 99%